2007
DOI: 10.1038/sj.sc.3102124
|View full text |Cite
|
Sign up to set email alerts
|

Epidural malignant lymphomas of the spine: collected experiences with epidural malignant lymphomas of the spinal canal and their treatment

Abstract: Subjects and methods: The epidural presentation in eight patients was heralded by motor signs (paraparesis and plegia), in one by a lesion of the posterior columns of the spinal cord (ataxia), and in three by pain. One patient was free of complaints and symptoms. The affected epidural area was diagnosed previously by myelography and computerized tomography (CT), and later by magnetic resonance (MR), over the course of which the location was verified as thoracic in eight patients, cervical in one, and lumbar in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…This indicated that rapid initiation of combined treatment is essential to achieve recovery of neurologic function. Besides neurologic decompression, the fundamental goal of treatment is life extension of the patients with the best quality of life (24). As it was impossible to resect the lesion entirely, the role of surgery in primary lymphoma of bone is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that rapid initiation of combined treatment is essential to achieve recovery of neurologic function. Besides neurologic decompression, the fundamental goal of treatment is life extension of the patients with the best quality of life (24). As it was impossible to resect the lesion entirely, the role of surgery in primary lymphoma of bone is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal epidural involvement has been reported in 0.8%-2.8% of all malignant lymphoma cases 7 and is most commonly present in the thoracic spine, followed by the cervical spine and less commonly in the lumbar spine. 8 These regions are may be the first site for a primary tumor, 2,9 or may be the area for a metastasis 10 while the disease is progressing.…”
Section: Discussionmentioning
confidence: 99%
“…Váróczy és mtsai klinikájuk 1996-2005 közötti beteganyagát bemutató dolgozatukban nem területi regiszter, hanem intézményi regiszterük adatait elemzik [8]. Idézett dolgozatuktól és az időnként felbukkanó esetbemutatásoktól eltekintve az extranodalis NHL-ek saját tapasztalatokat közreadó hazai irodalma lényegé-ben egy-egy szerv vagy szervrendszer lymphomás érin-tettségének az ismertetésére korlátozódik [9,10,11,12,13,14,15,16,17,18,19,20,21,22].…”
Section: Eredeti Közleményunclassified
“…Egyre gyakoribb megjelenésük megyénkben is megfi gyelhető. Évi átlagos számuk a vizsgált időszak első évtizedében (1983-1992) 5,5, a máso-dikban (1993-2002) ennek kétszerese (11,9) [3].…”
Section: Táblázatunclassified